Participatory Design as a Tool for the Urban Environment Development - E. Yu. Shcherbina; E. R. Klochkova (Управленческое консультирование)
Participatory planning is widely used worldwide as a tool of involving citizens in the processes of urban development, and it has also become more popular in Russia. The projects in Russia are implemented using foreign practices of participatory planning, thus there are N theoretical and methodological bases being developed. As a result, the involvement of citizens in the processes of urban development lacks in quality. This paper is devoted to organizing the participatory practices in the design of outdoor areas on the example of Saint Petersburg.the goal of the study is to create unifed rules of organizing participatory planning in Russia.The methodology is based on a systematic approach to the assessment of the outdoor areas quality, evaluation of citizens’ readiness to participate in participatory design and assessment of the availability of the projects implementation in this feld. The assessment of the outdoor areas quality was conducted with a method of a quality rating of a living environment.The evaluation of citizens’ readiness was based on a survey of the territory users. The method of the expert interview was used to assess the availability of the participatory planning projects implementation.The research results are formulated as recommendations for organizing the practices of participatory design in Russia.The following conclusions were made: the implementation of the recommendations provided for organizing the practices of participatory planning would increase the quality of outdoor areas and decrease the number of conﬂicts between stakeholders. Moreover, it would help in creating the local community, where the participants go through the transformation from the passive user to the active designer of the area.